ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PENGETAHUAN PERILAKU SEKSUAL PRANIKAH REMAJA DI SMA NEGERI 1 BATANGTORU TAPANULI SELATAN - Harahap, Tetty Misbah; Lubis, Ayu Ulfah Nur (Universitas Aufa Royhan, 2021)
This study result to analyse several variables that affect secsual behavior before marriage in SMA Negeri 1 Batangtoru south Tapanuli. The kind of the research used the survey through exsplanatori analytic research with cross sectional approach.total population of 738 students with a sample of 88 students. Biavriate analysis using the chi-square, with significance level α <0.05 and conviden level of 95%. Research results used test statistics chi-square show variabel that influental significantly against the knowledge of sexual behavior is a role parents (p=0.016), the role of peers (p=0.008) and exspusure information (p=0.019.variabel is have infiunce knowledge sexsual behavior towards. Expected teachers SMAN 1 Batangtoru can foster students to use media information correctly, increase students knowledge about reproductive health and increase extracurricular activities so that students spend more time on things that are more useful. The parents do not consider avoid doing communicatin with children about sexuality and reproductive health and be more open to the children, so that children get the aducation or correct information about sexuality and cared for each child’s activities and association child’s out board home.